Модификация способа подавления приемника-обнаружителя искусственным шумом - Макаренко, А. П.; Лихоман, А. А. (ХНУРЭ, 2012)
With the currently known methods of suppressing the receiver - the detector due to radiation of a legitimate part of the antenna channel "artificial noise". These methods are effective, but difficult to implement. For example, in one of these pseudo-random noise emission occurs at the physical level, and sifting it in the legitimate channel occurs at a representative level with the help of cryptographic algorithms